IMPLEMENTASI METODE WATERFALL DALAM MEMBANGUN MANAJEMEN KESISWAAN BERBASIS WEB PADA SUKU DINAS PENDIDIKAN WILAYAH I KOTA ADMINISTRASI JAKARTA TIMUR - Ari Pratitasari; Zaeni Miftah (STIKOM CKI, 2019)
Student data has an important role, especially in an educational institution. Because the data can be used as a reference for planning further education programs. The Education Office is a Work Unit of the Education Office in the City Administration in the implementation of educational activities in the City Administration Area. In this case the Education Office Tribe does not have the authority to manage student data which causes the institution must take a long time if at any time such data is needed because the Education Department Tribe must coordinate with the Implementing Unit (Satlak) to request data from the school, not yet a database for student data ona periodic basis, as well as frequent differences in data between one data with another. In this case the researchers used the waterfall method for making student management systems, and used UML (Unified Modeling Language) in designing student management systems and using SWOT analysis methods (Strength, Weakness, Opportunity, Threat) to analyze strengths, weaknesses, opportunitiesand threats. Based on the results of research from the student management system it can be concluded that this system can facilitate inter-educational institutions in monitoring student data and transfer student data that will be transformed into information that can be useful for those who use it.